In remembrance of the 100th performance of Beethoven's Ninth Symphony by the Bruno Kittelschen Chor, October 30, 1935 - Berlin Philharmoniker:::::::::::::::; Bruno Kittelsche Chor:::::::::::::::; Rentsch, Arno (author)::::::::::::::: (Germany; Berlin, 2020)
Program booklet for a performance of Beethoven's Ninth Symphony by the Berlin Philharmonic conducted by Wilhelm Fürtwanger. Includes the essay "'Die Neunte' und der Bruno Kittelsche Chor: eine Rückschau bei der 100. Aufführung" by Arno Rentsch, and the text of Schiller's "An die Freude."